Genetic diversity analysis of black pepper (Piper spp.) with RAPD markers - Rasphone, Sonexay; Hồ, Thị Hoàng Nhi; Dang, Thanh Long; Nguyen, Bao Le Quy; Truong, Hai Thi Hong (Hue University Journal of Science: Natural Science, 2022)
Black pepper is a well-known export commodity in Vietnam, but pepper production has been decreasing in recent years. The lack of knowledge about the origin and genetic characteristics of pepper varieties may create variety degradation and loss of product quality. Therefore, it is necessary to study the genetic diversity of existing local and imported pepper varieties and effectively propagate and create new varieties with high yields and quality. In this study, RAPD markers were used with 100 RAPD UBC primers to study genetic diversity. Twelve RAPD primers were selected to amplify 39 pepper cultivars, and 40 polymorphic DNA bands were created with sizes ranging from 200 to 1400 bp. Five of the 12 primers amplified all 39 cultivars. The genetic diversity of lines/cultivars in the pepper population is relatively high. The phylogenetic tree of the 39 cultivars has two branches showing similarity ranging from 41.8 to 51%. The first branch includes five pepper individuals, and the second consists of 34 individuals. There is a high diversity among the pepper cultivars in the same population.